The Cancer Chemopreventive and Therapeutic Potential of Tetrahydrocurcumin - Lai, Ching-Shu (Biomolecules, 2020)
In recent decades, cancer has been one of the leading causes of death worldwide. Despite advances in understanding the molecular basis of tumorigenesis, diagnosis, and clinical therapies, the discovery and development of effective drugs is an active and vital field in cancer research. Tetrahydrocurcumin is a major curcuminoid metabolite of curcumin, naturally occurring in turmeric. The interest in tetrahydrocurcumin research is increasing because it is superior to curcumin in its solubility in water, chemical stability, bioavailability, and anti-oxidative activity. Many in vitro and in vivo studies have revealed that tetrahydrocurcumin exerts anti-cancer effects through various mechanisms, including modulation of oxidative stress, xenobiotic detoxification, inflammation, proliferation, metastasis, programmed cell death, and immunity. Despite the pharmacological similarities between tetrahydrocurcumin and curcumin, the structure of tetrahydrocurcumin determines its distinct and specific molecular mechanism, thus making it a potential candidate for the prevention and treatment of cancers. However, the utility of tetrahydrocurcumin is yet to be evaluated as only limited pharmacokinetic and oral bioavailability studies have been performed. This review summarizes research on the anti-cancer properties of tetrahydrocurcumin and describes its mechanisms of action.